Correcting Class III Malocclusion Using Multiloop Edgewise Archwire (MEAW) Combines Temporary Anchorage Devices (TADs) With Modified Class III Elastics for Camouflage Treatment of in Adolescent: A Case Report - Lam Nguyen Le; Thao Thi Do; Khanh Phuong Vu Le (Case Reports in Dentistry)
Results: This case illustrated the use of TADs. MEAW combines TADs with modified Class III elastics for camouflage therapy. It is a potentially effective treatment option for adolescents diagnosed with Class III skeletal malocclusion.